A new wayside method for measuring and evaluating wheel-rail contact forces and positions. (15th December 2020) - Zhou, Wei; Abdulhakeem, Suleiman; Fang, Congcong; Han, Tianhu; Li, Guofei; Wu, Yitong; Faisal, Yahuza
Highlights: A new method for measuring wheel-rail contact forces as well as positions is proposed. Fitting formulas are derived to identify the lateral and vertical contact forces and positions from the rail web strains. Accurate measurement of the rail web strains is achieved by ingeniously designing and configuring the strain gauge circuit. The measurement technique is proved to be accurate and reliable in the FEA and laboratory tests. Abstract: Wheel-rail contact forces affect the safety, stability, economy and smooth running of the railway system. Measuring these forces and their positions remains a challenge due to the coupling interference of strain signals under multi-loading scenarios. This paper proposes a new wayside method to measure the magnitudes and positions of the lateral and vertical contact forces. Theoretical formulations for the contact forces and their positions with respect to the vertical strain sum and difference at rail web sides, are derived by the results of finite element analysis (FEA). A subtle strain gauge configuration is designed to measure the sum and difference of strains precisely. The robustness of the formulas is confirmed through extra FEA and the proposed method is validated by laboratory tests. The developed method provides an accurate and economic option for monitoring the wheel-rail contact status.